Endoscopic signs of gastroesophageal reflux disease with different hiatal hernias types - A. O. Nykonenko; Ye. I. Haidarzhi; О. М. Kiosov (Zaporozhye State Medical University, 2022)
A hiatal hernia occurs in 83-94 % of patients with gastroesophageal reflux disease (GERD). Difficulties in diagnosing endoscopic signs of gastroesophageal reflux with combination of the most common hiatal hernia types remain relevant. Untimely and inaccurate endoscopic interpretation of these pathological changes significantly reduces the effectiveness of treatment. The aim of the research was to study the endoscopic signs of gastroesophageal reflux disease with the most common hiatal hernia type I and type III. Materials and methods. The examination results of 153 patients with GERD and the most common hiatal hernia type I and type III at the stage of preparation for antireflux surgical treatment were analyzed. The age was 54.5 ± 11.3, there were 48 (31.4 %) men, 105 (68.6 %) women. In Group I - 85 patients with GERD and type I hiatal hernia, in Group II - 68 patients with GERD and type III hiatal hernia. A complete preoperative examination necessarily included endoscopy with chromoendoscopy (mainly NBI or FICE), biopsy from suspicious foci of the gastric mucosa and the lower third of the esophagus followed by histological analysis. Statistical processing and mathematical analysis of the obtained results were performed using the Statistica for Windows 13 (StatSoft Inc., No. JPZ804I382130ARCN10-J). For comparative analysis the arithmetic mean and standard deviation were calculated and presented as M ± s. Differences between groups were assessed using the sub-module "Difference tests" in the module "Basic statistics and tables". Differences at P < 0.05 were considered statistically significant. Results. In both groups, non-erosive forms of gastroesophageal reflux disease prevailed: 57 (67.1 %) and 39 (57.4 %) patients respectively. Both in Groups I and II, among the erosive forms there were mainly LA A stages of esophagitis - 20 (23.5 %) and 17 (25.0 %). СLE signs of the esophageal mucosa prevailed in Group I - 16 (18.8 %) patients, in Group II - 5 (7.4 %) patients. The proximal edges of the gastric folds, which are visualized in all patients, were considered the reference point for the true esophageal-gastric junction. Complicated course of GERD was noted in both groups of patients. Conclusions. Endoscopic signs of GERD with hiatal hernia type I or type III have characteristic features, the severity of which manifestation does not depend on the type. A reliable indicator of the true esophageal-gastric junction location is the proximal edge of the gastric folds. Complicated course of GERD occurs in both groups: Barrett's esophagus and Schatzki's ring predominate in the Group I, strictures and ulcers of the esophagus - in the Group II.